Towards implementing reactive scheduling for job shop problem - Zakaria, Zalmiyah; Deris, Safaai (2006)
Most of the research literature concerning scheduling concentrates on the static problems, i.e problems where all input data is known and does not change over time. However, the real world scheduling problems are very seldom static. Events like machine breakdown or bottleneck in some situation impossible to predict. Dynamic scheduling is a research field, which take into consideration uncertainty and dynamic changes in the real world scheduling problem. This paper gives an overview of the real problem occured in the filed of dynamic scheduling. Then we propose a hybrid genetic algorithm for solving the dynamic job shop problem.